O isolamento social e a busca da pureza: fé e razão - Cardoso, Leonardo Mendes (Estudos bíblicos, 2021)
This article discusses the relationship between the need for social isolation in times of outbreaks of serious infectious diseases and their relationship with religion and science, especially to achieve a better acceptance of inevitable separations and, therefore, a more satisfactory and savior result, both for the avoidance of contagion and for the closer observation of the occurring cases. The theme originates from the concrete situation relating to the COVID-19 pandemic and all the conflicts that have arisen there, especially the socioeconomic ones and the search for faith as the mainstay of life. The main objective is to understand the relationship between faith and scientific reason in moments of the same nature. The method employed is qualitative, descriptive and analytical through relevant literary reviews. As a problem, we ask about the legitimating role of the “word of God” seen in Lev 13:45-46 and Num 5:1-3 and the response reached seems to us to be indeed positive, leading us to the understanding that faith really reinforces the need for action more drastic in times of crisis.